Genetic diversity in hyacinth bean [Lablab purpureus (L.) Sweet] - Islam, MS; Rahman, MM; Hossain, MM; Mian, MAK; Hossain, T (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 9-14